Pengkondisian Cara Belajar Anak-Anak TK melalui Teori Belajar Sosial dengan Teknik Modelling - Amriana, Amriana; Munir, Misbahul; Cholil, Cholil (Jurusan Bimbingan dan Konseling Islam, 2021)
Kindergarten is an educational institution for children that lasts until children are 6 years old. At this age stage, children have a high curiosity about how to act properly in certain situations. For this reason, conditioning is needed to be able to control the development of behavior in each child. So, the purpose of this paper is to find out how to learn through social learning theory with efficient modeling techniques in shaping the desired behaviors in kindergarten age children. The subjects that will be observed are the students of TK Aisyiyah Bustanul Athfal 2 Jetis. The research method used is descriptive qualitative with data collection in the form of interviews and observations. The results of this study, positively, children can apply noble behavior through modeling techniques with live models, symbolic models and verbal description models.